Sistemática para combater perdas no processo produtivo de indústrias de pequeno porte de confecção - Santi, Sandro Nasser de (2013)
The companies have sought ever more efficient ways to organize to achieve their goals and, therefore, the search for a productive system that presents a good performance is one of important factors for the company to reach a stage really different efficiency. From this point of view, the main objective of this study is to develop a system for identifying production losses of small businesses in the garment sector Cianorte-Paraná, Brazil. Thus, from a survey of data from the factory floor, is intended to apply some tools of the Toyota Production System (STP) to suggest possible ways to eliminate waste and waste in the production process. Methodologically the research can be characterized as qualitative, quantitative and exploratory. For data collection visits were made to the company, where it was possible to maintain an informal dialogue with both the Production Engineer and with the staff directly involved with the production process and direct observation of the reality of the organization. The results show that the STP tools, mapping the value stream, identifies losses along the production process of the company, and, most importantly, the possibility of the production manager from this tool eliminate losses, tracing a new mapping, called future state, which relate opportunities for improvements in the production process, synchronized steps and leaving no gaps between them.